Knowledge-based development for cities and societies : integrated multi-level approaches - Metaxiotis, Kostas; Carrillo, Francisco Javier; Yigitcanlar, Tan. (Hershey, PA : Information Science Reference, 2010)
'This book presents a better knowledge and understanding of applying knowledge-based development policies, contributing to the theorizing of knowledge-based development and creation of knowledge societies'--Provided by publisher.
Includes bibliographical references.
Keywords: City planning; Knowledge management; Intellectual capital; Information technology -- Social aspects; Information society